Students’ Views on the Use of WhatsApp during Covid-19 Pandemic: A Study at IAIN Batusangkar - Munir, Sirajul; Erlinda, Rita; Afrinursalim, Hanif (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2021)
This study aims to describe students’ views on the use of WhatsApp in English Teaching Department classes during the covid-19 pandemic. The impact of the Coronavirus disease 2019 (Covid-19) pandemic is now beginning to spread to the world of education. This condition makes the students and the lecturers used online media or online learning much longer than expected. In the online learning process, WhatsApp is one of the most used applications. This study used qualitative research. The research population was all 270 students of the English Teaching Department of IAIN Batusangkar. The sample involved 168 students by using stratified random sampling technique. Slovin’s formula was used to measure the sample. The research instrument was questionnaires. It was designed in the type of closed-ended and open-ended forms. The questionnaire consisted of 21 statements. Then, to analyze the data from a closed-ended questionnaire, the researchers used Guttman Scale. Meanwhile, to analyze the open-ended questionnaire, the researchers classified students’ responses and then described the results. The finding of the study indicated that students’ views on the use of WhatsApp (WA) in English Teaching Department classes during the covid-19 pandemic mostly positive (73.2%) and the negative responses only (26.8%). Furthermore, students’ views on the use of WA includes WA as media in doing online learning process; WA as an educational media; WA as an evaluation and assessment benchmarks; WA as an application of sharing information; WA as the application to do group discussion; and WA as media to increase literation and to share learning materials. This research implies that WA could be used to do the online learning process because it empirically helps the students to get enthusiastically involved in learning activities.